P-084 OPEN PARASTOMAL HERNIA REPAIR: STOMA RELOCATION WITH CST, MODIFIED RIVES SUBLAY MESH TECHNIQUE WITH CST OR MODIFIED SUGARBAKER INTRAPERITONEAL MESH TECHNIQUE WITH CST. (13th October 2022) - Zuvela, M; Galun, D; Bogdanovic, A; Bidzic, N; Zivanovic, M; Bogdanovic, M; Zuvela, M; Zuvela, M
Abstract: Aim: To presents results of various open surgical techniques for parastomal hernia repair. Material and Method: Between January 2014 and January 2020, 22 patients with parastomal hernias were treated by three various operative techniques: a) stoma relocation using component separation techniques (CST); b) modified Rives sublay mesh technique with CST; c) modified Sugarbaker intraperitoneal composite mesh repair with or withouth CST. Stoma relocation and CST was performed in two patients, modified Rives sublay technique and CST in 15 patients and modified Sugarbaker technique with or without CST in five patients. Results: Hernia recurrence was developed in one of two patients treated by stoma relocation and CST and in two of 15 patients treated by modified Rives sublay mesh technique and CST. In five patients treated by modified Sugarbaker technique no complications occured. Mean follow up was 28 months. Conclusion: Modified Rives sublay technique with CST and modified Sugarbaker technique with or withouth CST provide good results in treatment of patients with parastomal hernia.